Human Chorionic Gonadotropin and Related Peptides: Candidate Anti-Inflammatory Therapy in Early Stages of Sepsis - Yoo, Sun Koo; Mehdi, Syed Faizan; Pusapati, Suma; Mathur, Nimisha; Anipindi, Manasa; Lunenfeld, Bruno; Lowell, Barbara; Yang, Huan; Metz, Christine Noel; Khan, Sawleha Arshi; Leroith, Derek; Roth, Jesse (Frontiers in Immunology, 2021)
Sepsis continues to be a major cause of morbidity, mortality, and post-recovery disability in patients with a wide range of non-infectious and infectious inflammatory disorders, including COVID-19. The clinical onset of sepsis is often marked by the explosive release into the extracellular fluids of a multiplicity of host-derived cytokines and other pro-inflammatory hormone-like messengers from endogenous sources (“cytokine storm”). In patients with sepsis, therapies to counter the pro-inflammatory torrent, even when administered early, typically fall short. The major focus of our proposed essay is to promote pre-clinical studies with hCG (human chorionic gonadotropin) as a potential anti-inflammatory therapy for sepsis.